A DETAILED STUDY OF THE PERFORMANCE AND OPTIMAL CHOICE OF ABRASIVE FOR WET GRINDING OF HIGH-ALLOYED STEELS - I. V. Bazuev; Yu. V. Pribytkov; I. A. Kovaleva; I. A. Ovchinnikova (Литьë и металлургия)
In the pipe-rolling shop, on the site of preparation of mandrels and disc saws were the centerless turning and grinding complex VT-8 «Hetran» for repair of mandrels are used, studies have been conducted to test experienced grinding belts. The choice was based on a comparative analysis of the work of experienced grinding belts with usual industrial grinding belts. The resistance of grinding belts for one mandrel is calculated. A positive result (economic effect) was obtained by using experienced grinding belts.